Clonal and constricted T cell repertoire in Common Variable Immune Deficiency - Ramesh, Manish; Hamm, David; Simchoni, Noa; Cunningham-Rundles, Charlotte (Clinical immunology (Orlando, Fla.), 2017)
We used high throughput sequencing to examine the structure and composition of the T cell receptor β chain in Common Variable Immune Deficiency (CVID). TCRβ CDR3 regions were amplified and sequenced from genomic DNA of 44 adult CVID subjects and 22 healthy adults, using a high-throughput multiplex PCR. CVID TCRs had significantly less junctional diversity, fewer n-nucleotide insertions and deletions, and completely lacked a population of highly modified TCRs, with 13 or more V-gene nucleotide deletions, seen in healthy controls. The CVID CDR3 sequences were significantly more clonal than control DNA, and displayed unique V gene usage. Despite reduced junctional diversity, increased clonality and similar infectious exposures, DNA of CVID subjects shared fewer TCR sequences as compared to controls. These abnormalities are pervasive, found in out-of-frame sequences and thus independent of selection and were not associated with specific clinical complications. These data support an inherent T cell defect in CVID. •CVID patients have a restricted TCR repertoire with fewer mutational changes.•CVID patients lack a highly modified population of T cells seen in healthy adults.•Patients have increased clonality of their T cells irrespective of clinical history.•Despite similar repertoires, CVID patients share fewer clones compared to controls.